2015
DOI: 10.1021/jacs.5b01613
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Solid-State Supercapacitor Based on a Metal–Organic Framework Interwoven by Electrochemically-Deposited PANI

Abstract: Metal-organic frameworks (MOFs) have received increasing attention as promising electrode materials in supercapacitors (SCs). Yet poor conductivity in most MOFs largely thwarts their capacitance and/or rate performance. In this work, an effective strategy was developed to reduce the bulk electric resistance of MOFs by interweaving MOF crystals with polyaniline (PANI) chains that are electrochemically deposited on MOFs. Specifically we synthesized cobalt-based MOF crystals (ZIF-67) onto carbon cloth (CC) and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
471
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 928 publications
(483 citation statements)
references
References 56 publications
11
471
0
1
Order By: Relevance
“…The latter may aggravate the mechanical properties of CPEs which can be reflected in the viscoelastic variations of polymer electrodes during electrochemical cycling [11][12][13]. Many CPEs have been studied for their appealing electrochemical properties [14], such as poly(3,4-ethylenedioxythiophene) (PEDOT) [15,16], polypyrrole (PPy) [17][18][19], polyaniline (PANI) [8,20] and polythiophene (PHT) [21,22]. PPy has been exploited in considerable amount of researches, due to its relatively higher pseudocapacitance and lower cost, as well as its particularly supreme flexibility in morphology and structure [23].…”
Section: Introductionmentioning
confidence: 99%
“…The latter may aggravate the mechanical properties of CPEs which can be reflected in the viscoelastic variations of polymer electrodes during electrochemical cycling [11][12][13]. Many CPEs have been studied for their appealing electrochemical properties [14], such as poly(3,4-ethylenedioxythiophene) (PEDOT) [15,16], polypyrrole (PPy) [17][18][19], polyaniline (PANI) [8,20] and polythiophene (PHT) [21,22]. PPy has been exploited in considerable amount of researches, due to its relatively higher pseudocapacitance and lower cost, as well as its particularly supreme flexibility in morphology and structure [23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its exceptional stability,124 reasonable biocompatibility,125, 126, 127 and high conductivity,128 its range of applications encompasses a variety of fields including biomedical engineering,129 flexible electronics,130, 131 and electromechanical engineering 132. Moreover, because of PANI's good biocompatibility and high conductivity, it also holds great promise for use in the engineering of electroactive tissues 133, 134.…”
Section: Polymeric Conductors and Semiconductorsmentioning
confidence: 99%
“…Organic compounds as additional materials Wang et al [106] reported a novel composite polyaniline-ZIF-67-carbon cloth (PANI-ZIF-67-CC) (Fig. 25).…”
Section: Additional Materials After Mofs Are Preparedmentioning
confidence: 99%